Antiviral and anti-inflammatory meroterpenoids: stachybonoids A–F from the crinoid-derived fungus Stachybotrys chartarum 952. Issue 79 (26th October 2017) - Zhang, Panpan; Li, Yongfang; Jia, Chunxiu; Lang, Jiajia; Niaz, Shah-Iram; Li, Jing; Yuan, Jie; Yu, Jianchen; Chen, Senhua; Liu, Lan
Abstract : Six new meroterpenoids, which have been named as stachybonoids A–F (1–3 and5–7 ), and three known phenylspirodrimanes (4, 8 and9 ) were isolated from the crinoid-derived fungus Stachybotrys chartarum 952. Abstract : Six new meroterpenoids, which have been named as stachybonoids A–F (1–3 and5–7 ), and three known phenylspirodrimanes (4, 8 and9 ) were isolated from the crinoid-derived fungus Stachybotrys chartarum 952. Their structures were established on the basis of extensive spectroscopic data (1D and 2D NMR, MS, and ECD), as well as the modified Mosher's method and single-crystal X-ray structural analysis. Compound1 exhibited inhibitory activity against the replication of dengue virus. Compounds4, 7, and8 exhibited moderate anti-inflammatory activity by inhibiting the production of nitric oxide (NO) in RAW264.7 cells activated by lipopolysaccharide, with IC50 values of 27.2, 52.5, and 17.9 μM, respectively.